Patients' shifting goals for deep brain stimulation and informed consent. (31st July 2018) - Kubu, Cynthia S.; Frazier, Thomas; Cooper, Scott E.; Machado, Andre; Vitek, Jerrold; Ford, Paul J.
Abstract : Objective: To determine using a repeated-measures, prospective design whether deep brain stimulation (DBS) results in changes in the importance of symptom and behavioral goals individually identified by patients with Parkinson disease (PD) before DBS surgery. Methods: Fifty-two participants recruited from a consecutive series completed a semistructured interview soliciting their rank-ordered symptom and behavioral goals and corresponding visual analog scales measuring perceived symptom severity and limits to goal attainment. Rank orders were reassessed at 2 times after DBS. Changes in rank order over time were examined with χ 2 analyses. The relationships between change in symptom severity/limits to behavioral goal attainment and change in rank order were examined with mixed-effects linear regression models. Results: Most participants changed the rank order of their symptom (81%) and behavioral (77%) goals 3 months after DBS surgery. Change in rank order of symptom goals was significantly related to change in severity ratings such that improvements in self-reported symptom severity were associated with reductions in rank. In contrast, no such relationship was evident for the behavioral goals. Conclusion: These data illustrate how patients' primary goals for DBS shift early in stimulation and highlight the important differences between symptom and behavioral goals. Changes in the rank order of symptom goals were related to changes in symptom severity, whereas subtler shifts in behavioral goals were unrelated to improvements after DBS. This observation suggests that DBS does not affect goals that may be more reflective of core personal values. The findings provide empiric data that can help improve the informed consent process.